2019
DOI: 10.1209/0295-5075/127/28001
|View full text |Cite
|
Sign up to set email alerts
|

Stability of DNA passing through different geometrical pores

Abstract: The recent years witnessed significant advances in nanopore technology and the DNA sequencing. One of the efficient methods for DNA sequencing is denaturation mapping of the DNA molecule that is trapped inside a cylindrical geometry. In this paper, we investigate the denaturation of homogeneous as well as heterogeneous DNA molecules which are confined in a conical as well as cylindrical geometric space. For the conically shaped confinement, we study the effect of the cone angle and the pore width on the melt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 48 publications
1
5
0
Order By: Relevance
“…next part of the study, we have used Gromacs package, version 4.0.4, to study the change in the average size of the 1 BNA molecule with the changing size (radius) of the cylinder.With the change in the cylinder's size (radius only), we have calculated the RMSD (root mean square deviation) values of the confined DNA at different temperatures. The RMSD calculations showed that the molecule is more stable when it is placed inside a cylinder.The results are trivial and well in agreement with the first part of the current investigation and our earlier work[1,2]. The reason for the stability is as follows: the decrease in the cylinder's radius, the confining wall becomes closer, which suppresses the molecule's entropy and hence the RMSD value decreases.…”
supporting
confidence: 92%
See 2 more Smart Citations
“…next part of the study, we have used Gromacs package, version 4.0.4, to study the change in the average size of the 1 BNA molecule with the changing size (radius) of the cylinder.With the change in the cylinder's size (radius only), we have calculated the RMSD (root mean square deviation) values of the confined DNA at different temperatures. The RMSD calculations showed that the molecule is more stable when it is placed inside a cylinder.The results are trivial and well in agreement with the first part of the current investigation and our earlier work[1,2]. The reason for the stability is as follows: the decrease in the cylinder's radius, the confining wall becomes closer, which suppresses the molecule's entropy and hence the RMSD value decreases.…”
supporting
confidence: 92%
“…Several researchers have extended the model to three-dimensions [17,18]. The PBD model has been extended to study the effect of molecular crowders as well as the effect of confinement on the thermal stability of DNA molecule [1,2,17]. The mathematical form of the model that contains N base pairs, is as follows:…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present manuscript, motivated by all these different kinds of experiments in different geometries, we attempt to understand the thermal stability of a DNA molecule that is confined in different geometries through a statistical model. The present manuscript is an following work of our recent published research work [32]. It helps to understand confinement effect more immensely.…”
Section: Introductionmentioning
confidence: 92%
“…This method opens up new possibilities for predicting the genome sequence by fusing the experimental approach with a computer simulation built on the Poland–Scheraga model [ 23 ], which assesses the sequence-dependent melting probability. In recent research, Maity et al [ 185 ] expanded these ground-breaking studies and made an effort to comprehend how DNA that is completely or partially confined in a nanochannel melts. They studied the melting of homogenous DNA in two distinct geometries: conical and cylindrical.…”
Section: Translocation Of Dna (Dna Passing Through Pores)mentioning
confidence: 99%